Mesures de la pauvreté en eau : analyse comparative et développement de l‘indice de pauvreté en eau - Hatem Jemmali (VertigO)
Most indicators of water scarcity are purely based on geophysical evaluation of water shortage. Such kind of water scarcity assessed are often called "physical shortage" ; by cons if more than one dimension is considered, other socio-economic and ecological factor should be taken in account in the assessment of the water resources availability. This resulted in the appearance of other type of shortage called the "economy shortage". This exploratory study on methods of assessing water scarcity confirms the interest of the multidisciplinary approach and the usefulness of the improved and simplified Water Poverty Index based on a combination of several indicators aggregated into five indices (Resources, Access, Capacity, Use and Environment).